Outcomes With the Use of Bag–Valve–Mask Ventilation During Out‐of‐hospital Cardiac Arrest in the Pragmatic Airway Resuscitation Trial. (27th March 2020) - Lupton, Joshua R.; Schmicker, Robert H.; Stephens, Shannon; Carlson, Jestin N.; Callaway, Clifton; Herren, Heather; Idris, Ahamed H.; Sopko, George; Puyana, Juan C. J.; Daya, Mohamud R.; Wang, Henry; Hansen, Matt
Abstract: Background: While emergency medical services (EMS) often use endotracheal intubation (ETI) or supraglottic airways (SGA), some patients receive only bag–valve–mask (BVM) ventilation during out‐of‐hospital cardiac arrests (OHCA). Our objective was to compare patient characteristics and outcomes for BVM ventilation to advanced airway management (AAM) in adults with OHCA. Methods: Using data from the Pragmatic Airway Resuscitation Trial, we identified patients receiving AAM (ETI or a SGA), BVM ventilation only (BVM‐only), and BVM ventilation as a rescue after at least one failed attempt at advanced airway placement (BVM‐rescue). The outcomes were return of spontaneous circulation (ROSC), 72‐hour survival, survival to hospital discharge, neurologically intact survival (Modified Rankin Scale ≤ 3), and the presence of aspiration on a chest radiograph. Comparisons were made using generalized mixed‐effects models while adjusting for age, sex, initial rhythm, EMS‐witnessed status, bystander cardiopulmonary resuscitation, response time, study cluster, and advanced life support first on scene. Results: Of 3, 004 patients enrolled, there were 282 BVM‐only, 2, 129 AAM, and 156 BVM‐rescue patients with complete covariates. Shockable initial rhythms (34% vs. 18.6%) and EMS‐witnessed arrests (21.6% vs. 11.3%) were more likely in BVM‐only than AAM but similar between BVM‐rescue and AAM. Compared to AAM, BVM‐only patients had similar ROSC (odds ratio [OR] = 1.29, 95% confidence interval [CI] = 0.96 to 1.73), but higher 72‐hour survival (OR = 1.96, 95% CI = 1.42 to 2.69), survival to discharge (OR = 4.47, 95% CI = 3.03 to 6.59), and neurologically intact survival (OR = 7.05, 95% CI = 4.40 to 11.3). Compared to AAM, BVM‐rescue patients had similar ROSC (OR = 0.73, 95% CI = 0.47 to 1.12) and 72‐hour survival (OR = 1.08, 95% CI = 0.66 to 1.77) but higher survival to discharge (OR = 2.15, 95% CI = 1.17 to 3.95) and neurologically intact survival (OR = 2.64, 95% CI = 1.20 to 5.81). Aspiration incidence was similar. Conclusions: Bag–valve–mask‐only ventilation is associated with improved OHCA outcomes. Despite similar rates of ROSC and 72‐hour survival, BVM‐rescue ventilation was associated with improved survival to discharge and neurologically intact survival compared to successful AAM.